Pengembangan Kewirausahaan Budidaya Burung Walet di Desa Bontoraja Kecamatan Gantarang Kabupaten Bulukumba - Risal Syam; Abd. Rasyid Masri (Universitas Islam Negeri Alauddin Makassar, 2023)
This type of research is included in qualitative research using a research approach method, namely the Islamic Community Development approach. Furthermore, the data sources are primary data and secondary data. Then the data collection methods used are observation, interviews, documentation. Then the data processing and analysis techniques are carried out through SWOT Analysis. The results showed that the swallow cultivation process includes 1) making swallow nests, in Bontoraja Village there are 6 buildings or swallow business houses. 2) inviting swallows, how to invite swallows easily using a voice recorder, Cd or cassette. 3) swallow breeding, 4) swallow livestock care, 5) swallow cage or house maintenance. Efforts to develop swallow cultivation entrepreneurship there are two factors, namely internal factors and external factors, swallow business in Bontoraja Village there are only 5 entrepreneurs in the development stage. Challenges and opportunities for entrepreneurship development are the challenges of pest disruptors such as rats. The opportunity is the price classification, and the large export market demand. The weaknesses are the high capital to build a building or swallow house and the different selling prices of swallow nests. The advantages of the swallow business in Bontoraja Village are the strategic location in building a swallow building or house and the abundance of food sources.